2018
DOI: 10.1055/s-0038-1666829
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative CT-Based Three-Dimensional Templating in Robot-Assisted Total Knee Arthroplasty More Accurately Predicts Implant Sizes than Two-Dimensional Templating

Abstract: Patient dissatisfaction after total knee arthroplasty (TKA) is a concern. Surgical error is a common, avoidable cause of failed TKA. Correct femoral and tibial component sizing improves implant longevity, clinical outcomes, knee balance, and pain scores. We hypothesized that preoperative three-dimensional (3D) templating for robot-assisted TKA (RA-TKA) is more accurate than two-dimensional (2D) digital templating. Prospectively collected data from 31 RA-TKAs were assessed to determine accuracy pertaining to im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 40 publications
0
28
2
Order By: Relevance
“…22 Computed tomography is also examined for preoperative planning, in which 3D reconstructions were superior over 2D conventional radiographs to determine preoperative TKA implant size. 23 The width of the foot can change after adulthood secondary to hallux valgus or other pathology or deformity of the foot. This could bias our results.…”
Section: Discussionmentioning
confidence: 99%
“…22 Computed tomography is also examined for preoperative planning, in which 3D reconstructions were superior over 2D conventional radiographs to determine preoperative TKA implant size. 23 The width of the foot can change after adulthood secondary to hallux valgus or other pathology or deformity of the foot. This could bias our results.…”
Section: Discussionmentioning
confidence: 99%
“…While custom cutting guides offer theoretical advantages, the majority of mid-to-long-term studies assessing their efficacy have demonstrated nonsuperiority [20][21][22][23][24][25][26] . Although the true value and cost-effectiveness of robotic technology have been debated, the use of robotic-arm assistance has demonstrated superiority to patient-specific instrumentation 27 and has shown the ability to improve TKA alignment in multiple studies 19,[28][29][30][31][32] . The findings of the current study, especially if alignment outlier status is linked to increases in implant failure in follow-up studies, may justify the increased use of these technologies in the future.…”
Section: Multivariate Analysismentioning
confidence: 99%
“…As a result of the link between implant alignment outliers and early implant failure, efforts have been made to optimize alignment with the use of robotic navigation and patient-specific instrumentation [19][20][21][22][23][24][25][26][27][28][29][30][31][32] . However, little work has been conducted to identify the primary surgeon-specific factors that drive these outliers in order to understand the optimal patient populations in which to utilize this expensive technology.…”
mentioning
confidence: 99%
“…Several studies have validated many of the goals that robotic arm assisted surgery set out to accomplish. Although the literature is in its infancy, key advantages of RTKA which have been supported by the literature include improved component positioning and restoration of limb mechanical axis, improved preoperative templating with computed tomography (CT) technology, and early improvements in short-term clinical outcomes compared to conventional instrumentation [5], [6], [7], [8], [9], [10], [11], [12], [13]. Several studies have also shown equal or improved safety compared to conventional instruments.…”
Section: Introductionmentioning
confidence: 99%